Association of Plasma Metabolic Biomarker Sphingosine-1-Phosphate With Cerebral Collateral Circulation in Acute Ischemic Stroke - Yu, Fang; Feng, Xianjing; Li, Xi; Liu, Zeyu; Liao, Di; Luo, Yunfang; Wei, Minping; Huang, Qin; Zhang, Lin; Xia, Jian (Frontiers in Physiology, 2021)
Background: The contribution of metabolomic profile to the cerebral collateral circulation in acute ischemic stroke (AIS) has not been fully outlined. Here, we conducted a metabolomics study to assess the relationship between metabolic biomarkers and the collateral status of AIS. Methods: A two-stage study was conducted from September 2019 to June 2021 in our hospital. There were 96 subjects including 66 AIS patients and 30 healthy controls in the discovery stage and 80 subjects including 53 AIS patients and 27 healthy controls in the validation stage. Collateral circulation was assessed by the Tan score based on computed tomographic angiography (CTA). Liquid chromatography-tandem mass spectrometry was used to identify differential metabolite markers. Then, an enzyme-linked immunosorbent assay (ELISA) was employed to detect the plasma levels of sphingosine-1-phosphate (S1P). Results: There were one hundred and fourteen differential metabolites between AIS patients and control groups, thirty-seven differential metabolites between good collateral circulation (GCC) and poor collateral circulation (PCC) groups. Pathway enrichment analysis revealed that arginine biosynthesis was the only statistically significant pathway between AIS and control groups, sphingolipid metabolism was the only statistically significant pathway between GCC and PCC groups. The differential metabolites sphinganine-1-phosphate (SA1P) and S1P belong to the sphingolipid metabolism. In the discovery stage, when GCC group compared to PCC groups, the receiver operating characteristic (ROC) analysis showed that plasma SA1P relative levels demonstrated an area under the curve (AUC) of 0.719 (95% CI: 0.582-0.834), and S1P levels demonstrated an AUC of 0.701 (95% CI: 0.567-0.819). In addition, both plasma SA1P and S1P relative levels showed significant negative correlations with 90-day modified Rankin Scale (mRS) score. In the validation sample, higher plasma S1P levels were independent predictors of GCC (p =0.014), and plasma S1P levels demonstrated an AUC of 0.738 (95% CI: 0.599-0.849) to differentiated patients with GCC from PCC. In addition, plasma S1P levels also showed significant negative correlations with 90-day mRS score. Conclusions: We first illustrated the association between plasma metabolic profiles and cerebral collateral circulation in AIS patients. Plasma S1P levels might be a potential diagnostic biomarker for predicting collateral circulation status in AIS patients.